The rights and wrongs of blood-brain barrier permeability studies: a walk through 100 years of history - Saunders, Norman R.; Dreifuss, Jean-Jacques; Dziegielewska, Katarzyna M.; Johansson, Pia A.; Habgood, Mark D.; Møllgård, Kjeld; Bauer, Hans-Christian (Frontiers in Neuroscience, 2014)
Careful examination of relevant literature shows that many of the most cherished concepts of the blood-brain barrier are incorrect. These include an almost mythological belief in its immaturity that is unfortunately often equated with absence or at least leakiness in the embryo and fetus. The original concept of a blood-brain barrier is often attributed to Ehrlich; however, he did not accept that permeability of cerebral vessels was different from other organs. Goldmann is often credited with the first experiments showing dye (trypan blue) exclusion from the brain when injected systemically, but not when injected directly into it. Rarely cited are earlier experiments of Bouffard and of Franke who showed methylene blue and trypan red stained all tissues except the brain. The term “blood-brain barrier” “Blut-Hirnschranke” is often attributed to Lewandowsky, but it does not appear in his papers. The first person to use this term seems to be Stern in the early 1920s. Studies in embryos by Stern and colleagues, Weed and Wislocki showed results similar to those in adult animals. These were well-conducted experiments made a century ago, thus the persistence of a belief in barrier immaturity is puzzling. As discussed in this review, evidence for this belief, is of poor experimental quality, often misinterpreted and often not properly cited. The functional state of blood-brain barrier mechanisms in the fetus is an important biological phenomenon with implications for normal brain development. It is also important for clinicians to have proper evidence on which to advise pregnant women who may need to take medications for serious medical conditions. Beliefs in immaturity of the blood-brain barrier have held the field back for decades. Their history illustrates the importance of taking account of all the evidence and assessing its quality, rather than selecting papers that supports a preconceived notion or intuitive belief. This review attempts to right the wrongs. Based on careful translation of original papers, some published a century ago, as well as providing discussion of studies claiming to show barrier immaturity, we hope that readers will have evidence on which to base their own conclusions.